2021
DOI: 10.1007/s10900-021-00995-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Toward Covid-19 and Vaccines Among a New York Haredi-Orthodox Jewish Community

Abstract: The Covid-19 pandemic has exposed the difficulty of the US public health system to respond effectively to vulnerable subpopulations, causing disproportionate rates of morbidity and mortality. New York Haredi-Orthodox Jewish communities represent a group that have been heavily impacted by Covid-19. Little research has examined their experience or perceptions toward Covid-19 and vaccines. We conducted a cross-sectional, observational study to explore the experience of Covid-19 among Haredim. Paper surveys were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Two studies report COVID-19 vaccine acceptance percentages in religious minorities in the US; an average willingness of 25% in Amish families of the Holmes County in Ohio ( 56 ) and 12% in Jewish Orthodox individuals in NY ( 30 ). Previous studies have shown that outbreaks of measles, rubella, and poliovirus have significantly affected the Amish community in Ohio, reflecting their lack of concern regarding the severity of the disease ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies report COVID-19 vaccine acceptance percentages in religious minorities in the US; an average willingness of 25% in Amish families of the Holmes County in Ohio ( 56 ) and 12% in Jewish Orthodox individuals in NY ( 30 ). Previous studies have shown that outbreaks of measles, rubella, and poliovirus have significantly affected the Amish community in Ohio, reflecting their lack of concern regarding the severity of the disease ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other predictors of unwillingness included avoiding dependence on the government, while some conservative families were not convinced as the bishop did not levy importance to it ( 56 , 82 ). Local governments in Pennsylvania, Ohio, and Indiana have set up vaccination facilities at health departments to increase turnout ( 30 ). However, an effective approach to spreading COVID-19 vaccine awareness and destigmatizing it in the Amish community will have to be in conjunction with the church leadership, and the Old Order Amish families which were unaffected by the religious doctrine ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies exploring uptake of SARS-CoV-2 vaccination among Orthodox and Haredi Jewish neighbourhoods in the US report lower likelihood of accepting vaccination and higher rates of hesitancy, and report that primary disseminators of vaccine information should be trusted stakeholders. 23 Considering how convenience and confidence affect use of vaccination services in this ethnic and religious minority, we examine the possibility of localising services in settings that are affected by outbreaks of vaccine-preventable disease. Emerging directly from the data analysis in our study, we define localising vaccination services as collaborating with community health organisations to deliver vaccines in ways that meet the situated (context-specific) needs and expectations of minority groups.…”
Section: Conceptual Frameworkmentioning
confidence: 99%